2015
DOI: 10.1007/s10551-015-2948-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Biases in Bank Lending: Lessons from Microcredit in France

Abstract: The evidence on gender discrimination in lending remains controversial. To capture gender biases in banks' loan allocations, we observe the impact on the applicants of a microfinance institution (MFI) and exploit the natural experiment of a regulatory change imposing a strict EUR 10,000 loan ceiling on microcredit. Descriptive statistics indicate that the presence of the ceiling is associated both with bank-MFI co-financing and with harsher treatment of female borrowers. To investigate causal links, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…This has to do both with additional costs and the lack of flexibility toward poorly documented clients Cull et al (2011). emphasize that complying with regulation is costly for MFIs and may lead them to exclude vulnerable borrowers, such as disadvantaged women (see alsoCozarenco & Szafarz, 2018). In contrast,Hartarska and Nadolnyak (2007) have found that regulation in general does not directly affect operational self-sustainability and outreach.…”
mentioning
confidence: 99%
“…This has to do both with additional costs and the lack of flexibility toward poorly documented clients Cull et al (2011). emphasize that complying with regulation is costly for MFIs and may lead them to exclude vulnerable borrowers, such as disadvantaged women (see alsoCozarenco & Szafarz, 2018). In contrast,Hartarska and Nadolnyak (2007) have found that regulation in general does not directly affect operational self-sustainability and outreach.…”
mentioning
confidence: 99%
“…The borrower's gender is an important variable in the context of microfinance since the industry claims that female empowerment is a leading motivation (Chaudhuri et al, 2020). Yet the facts are less clear-cut, since gender discrimination has been uncovered for larger loans (Garikipati et al, 2017;Cozarenco and Szafarz, 2018). The business activity reported by half of the borrowers is trade, while homeworking is claimed by 13%.…”
Section: Table 1 Gender Combinations In Our Samplementioning
confidence: 99%
“…Such studies have been conducted in different countries, in the U.S. (Fang & Munneke, 2016), Italy (Alesina et al, 2013;Bellucci et al, 2010;Calcagnini & Giombini, 2015), New Zealand (Fay & Williams, 1993), France (Brana, 2013), Germany (Stefani & Vacca, 2013), and Brazil (Agier & Szafarz). On the other hand, a few studies show that gender discrimination does not exist in the loan market (Cozarenco & Szafarz, 2015;Haines, Orser, & Riding, 1999). Cozarenco and Szafarz (2015) insist that approval for a microfinance loan was free from gender discrimination in France.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, a few studies show that gender discrimination does not exist in the loan market (Cozarenco & Szafarz, 2015;Haines, Orser, & Riding, 1999). Cozarenco and Szafarz (2015) insist that approval for a microfinance loan was free from gender discrimination in France. Haines et al (1999) showed that lending terms do not vary by gender in Canada.…”
Section: Literature Reviewmentioning
confidence: 99%